Application of a discrete element model to the analysis of granular soil recovery in an offshore tubular vibrocore - Wegener, Sam Bryant (Department of Civil Engineering, 2017)
As the human need for ocean resources accelerates, offshore geotechnics continues to grow and become ever more relevant. Seabed soil sampling is crucial in deep-water engineering projects or geological studies where a detailed knowledge of the seabed geology is required. Deep-sea vibrocoring is a relatively new offshore sampling technique. The system consists of a vertical, tubular core barrel with a sharp cutting edge at its lower end vibrated into the seabed by a high-frequency, low-amplitude vibratory motor. In the past, success of a coring operation has been judged primarily by the length of the recovered core. More recently, studies have given focus to the problems associated with achieving soil specimens in which the in-situ sedimentary structure is preserved. In practice, the core recovery ratio - defined as the ratio between the sampled length of core sediment and the length of core barrel penetrated into the soil - is frequently less than unity. Literature suggests that the physical processes governing the dynamic interaction between core barrel and soil are poorly understood. Through review of relevant literature, and the execution of both physical testing and numerical modelling, this study aimed to a) Develop a calibrated 30 discrete element model of a given vibrocore-soil system, and b) Investigate the soil mechanics phenomena influencing the disturbance and recovery of vibrocore soil samples.